Wider Economic Benefits from Communication-Cost Reductions: An Endogenous Growth Approach. (December 2013) - Bröcker, Johannes
The paper examines the impact of communication-cost reductions on growth and welfare by means of an endogenous spatial growth model. Policy makers favouring certain infrastructure investments often claim that such projects have growth-stimulating effects that generate 'wider impacts' in terms of welfare, over and above producer and consumer surplus effects, which are typically measured by traditional cost–benefit analysis. It is well understood that such wider impacts cannot arise in a first-best environment with perfect competition and zero externality. But, if the market allocation is not first-best, wider effects do occur and can in principle be positive or negative. Recent literature has shown that freight-cost or commuting-cost reductions can have wider impacts. While large infrastructure projects, such as high-speed trains, have no direct effect on freight costs and little effect on commuting costs, they are nevertheless conjectured to generate wider impacts. The typical argument is that high-speed trains reduce the costs of face-to-face contacts. This promotes innovation, which in turn exerts a positive externality on growth. To verify these claims rigorously, I have set up a Romer-type endogenous growth model for a multiregional economy. In this model innovators need to learn from the existing stock of knowledge by communicating with others across space, which is a costly activity. I show that, at the margin, reducing these costs generates a welfare gain that consumers value more than the cost reduction itself.